Ceria co-doped with calcium (Ca) and strontium (Sr) - Jaiswal, Nandini; Kumar, Devendra; Upadhyay, Shail; and et.al. (Springerlink.com, 2013)
Co-doped samples of Ce0.95-xCa0.05SrxO1.95-x, where (x = 0.00, 0.01, 0.02, and 0.03), have been prepared by auto-combustion method and characterized to explore their use as a solid electrolyte for intermediate temperature solid oxide fuel cells (IT-SOFCs). Crystal structure, microstructure, and ionic conductivity have been characterized by X-ray diffraction, scanning electron microscopy, and impedance spectroscopy, respectively. All the compositions have been found to be single phase. Results show that the samples co-doped with Ca and Sr exhibit higher ionic conductivity than the samples singly doped with Ca in the intermediate temperature range. Ce0.93Ca0.05Sr0.02O2-δexhibits maximum conductivity among all the compositions. This may be a potential candidate as a solid electrolyte for IT-SOFCs.
a potential candidate as a solid electrolyte for intermediate temperature solid oxide fuel cells
Keywords: Co-doping effect; Doped ceria electrolyte; Ionic conductivity; Solid oxide fuel cells